ANALISIS KELAYAKAN FINANSIAL USAHA PUPUK ORGANIK PADA UKM KOMONITAS NATURAL TANI DI DESA SIDERA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Aditya, Anang; Mappatoba, Marhawati; Muis, Abdul (AGROTEKBIS, 2018)
This research aims to know the feasibility of financial businesses organic fertilizer from waste cattle beef cattle on small and medium enterprises (SME) Komonitas Natural farmer Village Sidera Subdistrict Sigi Biromaru Sigi Regency based on criteria of Net Present Value (NPV) Net, B/C Ratio, Internal Rate of Return (IRR), Peyback Period (PP) analysis and research Sensivitas. Location determined intentionally (Purposive) with the consideration that SME Produce Natural Komonitas is the only group of farmers who are making business manage organic fertilizer. The respondent's determination was done deliberately (Purposive) with the number of respondents as much as 3 people consisting of 1 Chairman, 1 Treasurer and 1 employee part production. Methods of analysis using financial feasibility analysis, with some indicators that were used i.e. Net Present Value (NPV), the Net Benefit Cost Ratio (Net/B/C), Internal Rate of Return (IRR), Payback period (PP) analysis and Sensitivity calculation of  financial feasibility. Result of organic fertilizer on SME venture Komonitas Natural Farmers are financially viable to run based on the assessment criteria i.e. NPV, IRR, Net B/C and Payback Period, and sensitivity. Organic fertilizer venture acquire the value of NPV is IDR. 25.284.439 Net value, B/C of 3,48, value of 29.31% IRR is greater than the specified level of the discount rate, and PBP are before the project ends i.e. 2 years 9 months 8 days. The results of the sensitivity analysis also showed that organic fertilizers on SME venture Komonitas the Natural Farmer is still worth running and profit despite rising prices of raw materials amounting to 23 percent.